Pengaruh Pelatihan Pencegahan Covid-19 Terhadap Kepatuhan Protokol Pencegahan Covid-19 Pada Lansia Dengan Hipertensi - Risqi Widyasari; arif nurma etika; Susmiati Susmiati (PENA NURSING, 2022)
Menerima:Direvisi:Diterima:Kata kunci:Covid-19, Elderly, Training, Compliance Covid-19 is an infectious disease caused by a new type of coronavirus and is named Sars Cov 2. This virus attacks vulnerable groups, one of the vulnerable groups is the elderly. Mortality in vulnerable groups is high enough so that protective behavior needs to be carried out by the elderly to prevent the transmission of COVID-19. This study aims to prove whether there is an effect of COVID-19 prevention training on compliance with the Covid-19 prevention protocol in the elderly in Senganten Village, Gondang District, Bojonegoro Regency. This research is a quasi-experimental research. The population of this study was 30 people and the number of samples was 26 people who were selected using the Probabillity Sampling technique, precisely the Simple Random Sampling method. The test used in this study was the Wilcoxon test, which obtained a significant value or p Value = 0.317 > a = 0.05 in the control group and a significance value or p Value = 0.003 < a 0.05 in the treatment group, so it can be concluded that there is an effect of prevention training covid-19 on compliance with the covid-19 prevention protocol in the elderly with hypertension in Senganten Village, Gondang District, Bojonegoro Regency in 2021. The results of this study are expected that respondents comply with the covid-19 prevention protocol by washing hands with soap, using hand sanitizer, using masks and keeping a distance and it is recommended to health workers or cadres to provide periodic counseling to the elderly.